Cause analysis and nursing countermeasures of unplanned withdrawal of peripherally inserted central catheter in an elderly patient (老年患者PICC非计划拔管原因分析及护理体会) - CHEN Yunyun (程芸芸); CHEN Moyan (陈默岩); XU Bing (许冰) (Journal of International Translational Medicine Limited, 2021)
Complications such as unplanned withdrawal of catheter, catheter blockage and infection can arise during the placement of peripherally inserted central catheter(PICC). This paper analyzed the causes of unplanned extubation of PICC catheter in an elderly patient and summarized related nursing countermeasures. The occurrence of unplanned extubation is related to personal issues, fixation methods and other factors. The implementation of preventive measures plan can reduce the unplanned extubation of PICC in elderly patients, promote the continuous improvement of nursing quality, prolong the service time of catheter and avoid nursing risks. (经外周静脉置入中心静脉导管使用过程中会出现导管脱出、堵管、感染等相关并发症。本文总结了1例老年患者PICC非计划拔管事件的处理经验, 非计划拔管与患者自身原因、固定方法等多种因素有关。护理人员在置管前应先做好评估, 根据评估结果制定预防措施, 降低非计划拔管风险。)